An Amish Christmas promise [large type] - Brown, Jo Ann (Brown, Jo Ann. Green Mountain Blessings., 2019)
Secrecy kept her family safe- will she risk it all for a chance at love? Carolyn Wiebe discarded her Amish roots to hide her niece and nephew from their violent father. Yet when a hurricane crashes into their isolated Mennonite life, she can no longer keep the world at bay. With Christmas approaching, Amish carpenter Michael Miller wants to help her rebuild her home. But can their burgeoning love withstand the rising storm of her secrets?